2001
DOI: 10.1046/j.1439-0434.2001.00585.x
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Bacteria from Oilseed Rape in Relation to their Biocontrol Activity against Verticillium dahliae

Abstract: The potential of bacteria that are adapted to the oilseed rape root environment for use in the biological control of Verticillium dahliae, Kleb was investigated in both controlled and non-sterile growth conditions. Bacterial strains dominated by the red-pigmented members of enterobacteriaceae were isolated from thoroughly washed and air-dried root segments of symptomless young rape plants. Other associated strains found either belonged to Alcaligenes sp., Stenotrophomonas spp. and Pseudomonas spp. (Pseudomonas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
72
0
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 98 publications
(75 citation statements)
references
References 8 publications
2
72
0
1
Order By: Relevance
“…On the other hand, while studies on biological control of Verticillium wilts are available, they are again focused in herbaceous hosts and in just a small number of soil-borne fungi (i.e., Talaromyces, Trichoderma) or bacteria (i.e. Bacillus, Paenibacillus, Pseudomonas, Serratia, Streptomyces) species which have so far been demonstrated to be effective BCA against V. dahliae (Jordan and Tarr 1978;Leben et al 1987;Berg et al 1994;Madi et al 1997;Alström 2001;Nagtzaam et al 1998;Narisawa et al 2002;Tjamos et al 2004Tjamos et al , 2005Antonopoulos et al 2008;Uppal et al 2008;Erdogan and Benlioglu 2010;Meschke and Schrempf 2010). Finally, arbuscular mycorrhizal fungi (i.e.…”
Section: Use Of Beneficial Microorganisms and Microbial Antagonists Tmentioning
confidence: 99%
“…On the other hand, while studies on biological control of Verticillium wilts are available, they are again focused in herbaceous hosts and in just a small number of soil-borne fungi (i.e., Talaromyces, Trichoderma) or bacteria (i.e. Bacillus, Paenibacillus, Pseudomonas, Serratia, Streptomyces) species which have so far been demonstrated to be effective BCA against V. dahliae (Jordan and Tarr 1978;Leben et al 1987;Berg et al 1994;Madi et al 1997;Alström 2001;Nagtzaam et al 1998;Narisawa et al 2002;Tjamos et al 2004Tjamos et al , 2005Antonopoulos et al 2008;Uppal et al 2008;Erdogan and Benlioglu 2010;Meschke and Schrempf 2010). Finally, arbuscular mycorrhizal fungi (i.e.…”
Section: Use Of Beneficial Microorganisms and Microbial Antagonists Tmentioning
confidence: 99%
“…Endophytic bacteria such as Pseudomonas and Bacillus spp. were found to be potent BCAs against fungal pathogens on crops such as cotton, oilseed rape, tomato, cucumber and peas (Chen et al, 1995;Alstrom, 2001). In addition, some members of the genus Bacillus such as B. cereus are often considered as microbial factories of biologically active molecules that are potential inhibitors of fungal growth (Pérez-García et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Many of these specialized compounds, such as antibiotics, are either liquid or solid at room temperature, and little is known about volatiles (with molecular masses less than 300 Da, low polarity, and a high vapor pressure) that can act as antibiotics and cause growth inhibition or have more deleterious effects on organisms. The microbial world synthesizes and emits many volatile compounds (1,3,4,6,16,17). We previously showed that rhizobacterial isolates of Serratia plymuthica, Serratia odorifera, Stenotrophomonas maltophilia, Stenotrophomonas rhizophila, Pseudomonas fluorescens, and Pseudomonas trivialis emit complex blends of volatiles that inhibit the growth of Rhizoctonia solani (12).…”
mentioning
confidence: 99%